Current Trends in the Management of the Brachial Plexus Injuries - Mohamed ElSabaie (Egyptian Spine Association, 2013)
Background Data: BPIcomprise about one third of all peripheral nerve injuries and seen in just more than 1% of patients presenting to a trauma facility. They may range from weakness or paralysis of the shoulder and/or elbow to complete paralysis and loss of feeling in the entire upper limb. Over the last two decades, refinements in microsurgical techniques, and significant advances in the concepts of peripheral nerve repair and reconstruction have greatly expanded treatment options for these otherwise devastating injuries. Traction of the shoulder or arm, often with lateral flexion of the neck in the opposite direction, Penetrating trauma to the neck or the shoulder, and Birth-related paralysis are the most common causes of the BPI. They divided into supraclavicular and infraclavicular lesions. MRI of the brachial plexus and cervical spine, and myelography with CT, are the key of the final differentiation of the exact pathology. The surgical intervention may be indicated if there is little evidence of progressive spontaneous recovery of motor and sensory function by three months following injury, but no longer than 6 months. However, early surgical exploration is frequently indicated in penetrating or open injuries. Purpose: The aim of the work is to update our knowledge about the current measures and the new techniques of management of the brachial plexus injuries Study Design: Review article Material and Methods: This study was done via the electronic searching on the clinical trials, systemic midline reviews through the PubMed clinical queries, WHO, Cochrane Collaboration and Evidence Based Medicine since 2008 till 2013. Results: Analysis of the reviewed studies showed that recovery is very promising to the BPI patients that were faced the loss of hope of recovery in the previous years. Conclusion: By applying the triad of recent imaging measures, proper management guidelines and excellent rehabilitation programs, the patient will gain the maximum functional outcome. While complete recovery is often difficult to obtain, an acceptable level of restored function is possible, and patients need to be made fully aware of realistic therapeutic goals. (2013ESJ54)